Polymorphism of Toll-like Receptor-9 (TLR9) rs187084 (−1486T>C) in Iraqi Patients with Type 2 Diabetes Mellitus - Kashmer, Shahad Dyaa Slman; Ahmed, Intisar Hussein (American Journal of Biology and Natural Sciences, 2025)
This study investigated the association between the Toll-like receptor 9 (TLR9) rs187084 (−1486T>C) polymorphism and the risk of type 2 diabetes mellitus (T2DM), as well as its impact on serum TLR9 levels, in a cohort of 45 T2DM patients and 35 healthy controls. Genotyping revealed significant differences in the distribution of CC, CT, and TT genotypes between groups. The TT genotype was significantly more prevalent in T2DM patients (P = 0.004), indicating increased disease susceptibility, while CC and CT genotypes were underrepresented, suggesting protective effects. Allele frequency analysis supported this association: the T allele was more frequent in patients (46.67%) than controls (22.86%), while the C allele predominated in controls (77.14%) (P = 0.018). Genotypic risk analysis indicated that TT genotype carriers had a sevenfold increased risk of T2DM (OR = 7.111, 95% CI: 1.889–26.76, P = 0.007). Gender-specific analysis revealed a stronger association in females (OR = 10.00, P = 0.040) and a protective role of the CC genotype in males (OR = 0.153, P = 0.03). The recessive inheritance model showed a significant protective effect (OR = 0.1406, P = 0.003), while dominant and over dominant models showed non-significant trends. These findings suggest that TLR9 rs187084 polymorphism contributes to T2DM susceptibility via immune-inflammatory pathways and may serve as a potential biomarker for risk stratification and targeted therapies.